Imkān Al-Ru’yah by Ma’şūm Ali - Nasir, M. Rifa Jamaludin (University of Muhammadiyah Sumatera Utara, 2022)
This research review the thinking of Ma’şūm Ali about Imkān al-Ru’yah(The concept of New Moon Visibility, example and It’s Application in Determination of the beginning Hijriyah month). This study will discussthree points. First, How the perspective of modern astronomy is about Imkān al-ru’yah criterion by Ma’şūm Ali . Second, how the implementation of the criterion is and what the contribution of the concept Imkān al-ru’yah by Ma’şūm Ali is for the determination of the beginning Hijriyah Month in Indonesia. The object of this study is the thought of Ma’şūm Ali about Imkān al-ru’yah. The approach taken is astronomical approach . The method of data analysis is using deduction holistika method .The results showed , first; the construction of Imkān al-ru’yah by Ma’şūm Ali is acceptable and applicable because of the astronomical formulations used as guidelines is correspond to the concept and theory of Sun and Moon movement. Second, implementation of criteria Imkān al-ru’yah practiced by Ma’şūm Alihimself. The contribution of the Imkān al-ru’yah criterion by Ma’şūm Ali is that this theory can be applied as an Imkān al-ru’yah theory in Indonesia based on theoretical data and empirical applications.